Terwilliger Algebras of Group Association Schemes of Matrix Groups - Hamid, Nur ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2025)
This paper investigates the Terwilliger algebras of some group association schemes related to matrix groups. We obtain the structure of the Terwilliger algebras for the general and the special linear group of 2×2 matrices over the field of order 5. In particular, we determine the Wedderburn decomposition of these algebras.